(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2017)
Intelligent transportation systems (ITS) are advanced applications which, without embodying intelligence as such, aim to provide innovative services relating to different modes of transport and traffic management and enable various users to be better informed and make safer, more coordinated, and ’smarter’ use of transport networks. Highway travel is the lifeblood of modern industrial nations. The larger roads are sorely over burdened: around the major cities, heavy usage slows most peak-hour travel on freeways to less than 60 kilometers per hour. In all excessive traffic causes more than five billion hours delay every year; it wastes countless gallons of fuel and needless multiplies exhaust emission. The main goal of this paper is to make the experience of driving less burdensome and accident less, especially on long trips. This can be achieved by making the highway itself part of the driving experience and integrating roadside technologies that would allow the overburdened highway system to be used more efficiently. The automobile will have automatic throttle, braking and steering control.